Eco enzyme and its benefits for organic rice production and disinfectant - Hasanah, Yaya (Journal of Saintech Transfer, 2021)
Eco enzyme is a fermented liquid from organic waste fruits, vegetables, and other organic waste which is very useful for agriculture, health, and households. One of Deli Serdang villages that are very vulnerable to Covid-19 is Karang Anyar Village, located in Beringin District, only about 5 km from Kuala Namu International Airport. On the other hand, in Karang Anyar Village, there is a Mekar Pasar Kawat farmer group that cultivates organic rice that needs liquid organic fertilizer (LOF). This community service aims to educate the public about using an eco enzyme from household waste as liquid organic fertilizer (LOF) and disinfectant. Implementing community service that is carried out is training and practice of making eco enzyme and its benefits, direct practice of demonstration plot of rice cultivation by utilizing eco enzyme as LOF. The results are training and mentoring in making eco enzyme based on household waste, training and hands-on practice on applying eco enzyme in the environment as disinfectant, training, and direct demonstration plot rice cultivation by utilizing eco enzyme produced as organic fertilizer liquid